Load Balancing and Fail Over MikroTik Implementation Using Per Connection Classifier (PCC) on Two Internet Providers Interconnection - Wiharti, Wiwik; Rimra, Ihsan Lumasa; Rifka, Silfia; Hidayatullah, Ikhram; Kasmar, Andre Febrian (International Journal of Advanced Science Computing and Engineering, 2023)
Load balancing is tasked with dividing and balancing the traffic load on two or more ISPs in a balanced way so that the output obtained when using this technique is to maximize throughput, minimize response time and avoid overload on one ISP line when one of the ISPs experiences a disconnection. This can be seen from the automatic connection switching to an active ISP gateway, so that network performance continues to run normally. Throughput testing in the morning, afternoon, and evening showed very good value changes after load balancing was applied. Delay and Packet Loss tests also show a change in value from bad to very good after the implementation of the Load balancing system. The results of this study indicate that in measuring network performance for conditions of delay, packet loss, jitter and throughput before and after system implementation using load balancing and failover with the Per Connection Classifier (PCC) method, different results were found